Етико-психологічні аспекти комунікаційних процесів у бізнесі - Химиця, Наталія; Керенович, Лілія; Марців, Марія (Видавництво Львівської політехніки, 2017)
This article highlights influence of factors of different nature on the activity in the sphere of business relations, in particular business from the point of view of psychology, ethics and socionics, as its main directions.
Keywords: комунікація; бізнес; психологія; етика; соціотип